Penegakan Hukum Pidana Terhadap Pencurian Arus Listrik Oleh Nasabah Studi Kasus PT. PLN UP3 Jambi - Rayhan Ichsan; Elizabeth Siregar; Erwin (CV. ITTC INDONESIA, 2025)
This study aims to determine the law enforcement against electricity theft in Jambi City and to determine the obstacles to law enforcement against electricity theft committed by customers in Jambi City. In this study, the problems reviewed are regarding 1) How is the law enforcement against electricity theft in Jambi City, 2) What are the obstacles to law enforcement against electricity theft committed by customers in Jambi City. The research method used in this writing is the empirical legal approach. Empirical legal research aims to determine how the law is implemented in society, by looking at the realities in the community so as to know how the law works. This study uses qualitative research techniques with empirical legal research methods that can be carried out in 3 (three) ways, namely through interviews, questionnaires, questionnaires and observations. Criminal law enforcement against electricity theft in Jambi City still faces challenges, both in terms of social, cultural, and technical aspects. Although the regulations have clearly regulated criminal sanctions for perpetrators of electricity theft, the implementation of law enforcement is still inconsistent. PLN UP3 Jambi has conducted various detection efforts ranging from field inspections, public reports, to real-time digital monitoring. Suggestions for PLN to strengthen internal supervision to avoid collusion, develop smart meter technology and more sophisticated monitoring systems, and increase transparency and education to the public about the impacts and sanctions for electricity theft.